If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(4w + 1) + -2w = 5w + -1 Reorder the terms: 2(1 + 4w) + -2w = 5w + -1 (1 * 2 + 4w * 2) + -2w = 5w + -1 (2 + 8w) + -2w = 5w + -1 Combine like terms: 8w + -2w = 6w 2 + 6w = 5w + -1 Reorder the terms: 2 + 6w = -1 + 5w Solving 2 + 6w = -1 + 5w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-5w' to each side of the equation. 2 + 6w + -5w = -1 + 5w + -5w Combine like terms: 6w + -5w = 1w 2 + 1w = -1 + 5w + -5w Combine like terms: 5w + -5w = 0 2 + 1w = -1 + 0 2 + 1w = -1 Add '-2' to each side of the equation. 2 + -2 + 1w = -1 + -2 Combine like terms: 2 + -2 = 0 0 + 1w = -1 + -2 1w = -1 + -2 Combine like terms: -1 + -2 = -3 1w = -3 Divide each side by '1'. w = -3 Simplifying w = -3
| 100/×=-4 | | -10x=8x-7 | | 3x-59=34 | | 1/2x-400=5000 | | 2/7=35/h | | X+9-4x=-3x-3 | | g=2(2)+1 | | 4x+7-2x=-4 | | x+0.2x=53 | | 1/2-400x=5000 | | 4/5x=-141/35 | | g=2(0)+1 | | 10x-131=5x-6 | | 12/y=30/9 | | g=2(-1)+1 | | 7x+6=66 | | 6x-7+2x+8=x+5-2x+12 | | g=2(-2)+1 | | -3x+4=5x-8 | | (6x-1)/2=9 | | (x+12)(x-1)=2(x-6)-20 | | 6x+3*(-3)=9 | | 6x-1/2=9 | | -7.8x+2.4x=40 | | -4+4X=-16+13 | | 6*2+3y=9 | | 2x-5+4x+10=21 | | 24x^3+8x^2=100x^2+-28x | | -2(-4-3x)=-28 | | 6x+1=12-2x | | 7*log(3x)+3log(5x)=15 | | 20+9b=38 |